Hybrid Control Scheme for Anaerobic Digestion in a CSTR-UASB Reactor System - Tawai, Atthasit; Kitsubthawee, Kanyarat; Panjapornpon, Chanin; Shao, Weiming (Applied Science and Engineering Progress, 2020)
Anaerobic digestion is an important wastewater treatment technology for industrial wastewater. To achieve the target of global environmental regulation, process control plays an important role in the system operation. The control system for anaerobic digestion process is generally applied to each reactor separately without consideration of variables that mutually affect the operation of the other one. This work proposes a hybrid control scheme for a CSTR-UASB reactor system described by a PDE-ODE model. The CSTR system is employed to rapidly reduce the inlet COD concentration while the UASB reactor is used to accurately regulate the outlet COD concentration of the system. An input-output (I/O) linearization and proportional-integral (PI) control techniques are applied to formulate the control scheme for the process. The distributed variables are applied to the developed control system for handling the spatially distributed dynamics of the bacterial biomass. The COD concentration of both reactors are manipulated through the dilution rate and feed flow rate to achieve the desired targets. Simulation results of the closed-loop system illustrate that the developed control scheme regulates the controlled outputs to follow the desired trajectories and manipulate the control problems effectively.